Innovation in Electronic-Based Archive Arrangement at the Personnel and Human Resources Development Agency of West Sumbawa Regency - S. Syahrel; Muammar Khadafie (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the implementation of electronic-based archival arrangement innovations at the West Sumbawa Regency Personnel and Human Resources Development Agency (BKPSDM) as an effort to increase the effectiveness of personnel document management. The research uses a descriptive qualitative approach through in-depth interview techniques, observations, and documentation studies. The results of the study show that the application of an electronic archive system is able to increase time efficiency, facilitate access to information, and reduce the risk of document loss. This innovation also encourages transparency and accountability in public services. However, there are several obstacles, including the limitation of human resources who have information technology competencies and the need for a more stable network infrastructure. These findings affirm the importance of apparatus capacity strengthening strategies and technological support for the sustainability of digital innovation in personnel archive governance.